Mixed Embeddedness and Institutional Constraints: A Bibliometric Analysis of Ethnic Entrepreneurship (2015–2025) - Thanh Thuy Tran, Nguyen; Reicher, Zsuzsánna Regina (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
As global economies prioritize sustainable governance, rising institutional standards have created a "cost floor" that threatens the survival of ethnic SMEs, particularly within the rigid regulatory landscape of Europe. This study conducts a systematic bibliometric analysis of 492 articles (2015–2025) from the Web of Science to map how academic literature tracks these institutional constraints. The mapping identifies a significant geographical asymmetry, where a dominance of North American studies overlooks the specific structural pressures found in European welfare states. A primary objective is to investigate an identified "theoretical leapfrog" in the field, where research transitions from sociological enclave studies directly to psychological resilience while bypassing the actual mechanics of institutional transition. Finally, by justifying keywords like "Mixed Embeddedness" and "Institutional Constraints," the study identifies a critical gap in regulatory inclusivity and provides a data-driven roadmap for future research into ethnic business survival.